Boardgame : immortal - Yeo, Jonas Pei Xun (2016)
The objective of my project is to create a board game with mechanics inspired by thorough research in the topic of Reincarnation. Due to the religious and mythical nature behind the concept of Reincarnation, research extended to the major religions of the world and their individual ideas of Salvation or Immortality. It also led into a study of various myths of Life-Death-Rebirth Deities and Heroes that have attained Immortality. These myths were then broken using Joseph Campbell’s Monomyth where the stages of spiritual progression were identified. Through the Hindu concept of the 4 Yogas, 4 final myths were chosen to be represented within the board game. At this point, the game mechanics have been finalized, and will explore themes such as Karma, Fame and Sin in an attempt to guide players spiritually and morally through game play. Essentially, through this board game, players will be able to find out what Salvation and Immortality mean to themselves, while being exposed to the concepts of Reincarnation and Karma.